Review of Chinese Oligaphorurini (Collembola, Onychiuridae) with descriptions of two new Palaearctic species - Sun, Xin (Pensoft Publishers, 2012)
Abstract. A checklist of Chinese Oligaphorurini is given. Two new Chinese species, Micraphorura changbaiensis sp. n. and Oligaphorura pseudomontana sp. n., are described from Changbai Mountain Range. Micraphorura changbaiensis sp. n. has the same dorsal pseudocelli formula and number of papillae in Ant. III sensory organ as Micraphorura uralica, but they can be easily distinguished by number of chaetae in Ant. III sensory organ, ventral pseudocelli formula, ventral parapseudocelli formula, number of pseudocelli on subcoxa 1 of legs I–III, dorsal axial chaeta on Abd. V and number of chaetae on tibiotarsi. Oligaphorura pseudomontana sp. n. is very similar to the species Oligaphorura montana having an increased number of pseudocelli on body dorsally, well marked base of antenna with 1 pseudocellus and 3 pseudocelli outside, subcoxa 1 of legs I–III with 1 pseudocellus each, dorsally S-chaetae formula as 11/011/22211 from head to Abd. V, S-microchaeta present on Th. II–III, claw without inner teeth and with 1+1 lateral teeth, and unguiculus with basal lamella; but they can be separated easily by the number of pseudocelli on Abd. V and VI terga, parapseudocelli on the body, number of chaetae on Th. I tergum, and number of chaetae on tibiotarsi. A key to Chinese species of Oligaphorurini is provided in the present paper.